Non- participation of HIV positive men in support groups for people living with HIV/AIDS in the King Sabata Dalindyebo (KSD) Municipality: Eastern Cape Province; an exploratory study - Canti-Sigaqa, Vuyokazi (University of Limpopo (Medunsa Campus), 2010)
Introduction: Men living with HIV and AIDS generally do not participate in support groups even though evidence supports their effectiveness as a source of valuable support for people living with HIV and AIDS PLWHA). Study Aim: The aim of the study was to explore reasons for the reluctance of HIV positive men to attend support groups and examine their perceptions and understanding of the benefits of attending support groups for PLWHA Methods: A qualitative descriptive approach was used for this study. A total of five (5) focus group discussions was conducted with HIV positive males receiving ART from Infectious Disease Clinic (IDC) at King Sabata Dalindyebo Municipality in Mthatha Data analysis: Thematic content analysis was used to analyse data from the focus groups, using Nvivo8 a qualitative soft ware used for data analysis and coding revealed 10 themes with their sub categories. Findings: Findings of the research indicate that participants perceive support groups as being helpful to PLWHA. Participants have a broad and positive understanding of the benefits of participation in support groups. Reported barriers to participate in support groups included lack of access to support groups in local communities which affected the distance travelled to support groups, inconvenient and awkward timing of the support group sessions and attending mixed gender support groups which was not acceptable for participants. Personal reasons for non participation included fear of potential disclosure of HIV status due to lack of confidentiality in support groups and perception that support from families and friends was adequate. Recommendation: The study recommends the introduction of men only support groups facilitated by male to enhance men’s participation in HIV and AIDS programmes, and thus create an enormous contribution in the curb of the spread of the disease.
Thesis (MPH)--University of Limpopo, 2010.
Keywords: HIV positive; HIV/AIDS